Bureaucrats, Tournament Competition, and Performance Manipulation : Evidence from Chinese Cities - Xu, Gang (Washington, DC: World Bank, 2022)
Tournament competition is viewed as motivating bureaucrats in promoting growth. This paper examines how this incentive leads to economic performance manipulation. Using data from Chinese cities, the analysis shows that performance exaggeration increases over the course of the first term of the top bureaucrat, peaking in the last year of his or her term. Winning a tournament competition is behind this performance manipulation: political rivals reinforce each other in exaggerating performance, and political competition intensifies the tendency for manipulation. Performance exaggeration leads to higher chances of promotion, but the ratchet effect (that is, better performance today leading to a higher target tomorrow) and the potential to blame predecessors induce restraint. A good local institutional environment also restrains performance manipulation.